Truman and the Democratic Party - Savage, Sean J. (Book collections on Project MUSE., 2015)
What best defines a Democrat in the American political arena -- idealistic reformer or pragmatic politician? Harry Truman adopted both roles and in so doing defined the nature of his presidency. Truman and the Democratic Party is the first book to deal exclusively with the president's relationship with the Democratic party and his status as party leader. Sean J. Savage addresses Truman's twin roles of party regular and liberal reformer, examining the tension that arose from this duality and the consequences of that tension for Truman's political career. Truman saw the Democratic party change du.